Development of Problem Based e-Module to Train Higher Order Thinking Skills on Temperature and Heat Material - Herdila, Preti; Herlina, Kartini; Anggreini, Anggreini (Jurnal Penelitian Pembelajaran Fisika, 2024)
The development of science and technology has become very sophisticated, where science and technology has had a significant impact on various areas of life, especially education. In this modern era, teachers must be able to take advantage of developments in technology and information in learning, for example using it as a learning medium to convey learning material to students. In fact, in schools the use of learning media to attract students' attention has not been implemented effectively and efficiently. So this research aims to develop a valid, practical and effective problem-based e-Module on temperature and heat material to train students higher order thinking skills. This research uses the Design and Development Research type of research which consists of four research stages, namely analysis, design, development, and evaluation using assessments of validity tests, practicality tests consisting of readability tests, student response tests, and perception tests. teachers, the effectiveness test consists of a normality test, N-Gain, and Paired Sample T-Test. In the validity test results, an average score of 3.50 was obtained in the very valid category. The results of the practicality test in the readability test obtained an average score of 82.64, which was categorized as very readable, in the student response test, an average score of 82.7 was obtained, which was categorized as very good, and in the teacher perception test, an average score of 83,3 was obtained which is categorized as very good. Meanwhile, for the effectiveness test based on the results of the students' N-Gain pretest-posttest, an average score of 0.45 was obtained in the medium category.